Visual acuity, endothelial cell density and polymegathism after iris-fixated lens implantation - Nassiri, Nader (Clin Ophthalmol, 2018)
PURPOSE: The purpose of this study was to evaluate the visual acuity as well as endothelial cell density (ECD) and polymegathism after iris-fixated lens (Artiflex(®) AC 401) implantation for correction of moderate to high myopia. PATIENTS AND METHODS: In this retrospective cross-sectional study, 55 eyes from 29 patients undergoing iris-fixated lens implantation for correction of myopia (−5.00 to −15.00 D) from 2007 to 2014 were evaluated. Uncorrected visual acuity, best spectacle-corrected visual acuity, refraction, ECD and polymegathism (coefficient of variation [CV] in the sizes of endothelial cells) were measured preoperatively and 6 months postoperatively. RESULTS: In the sixth month of follow-up, the uncorrected vision acuity was 20/25 or better in 81.5% of the eyes. The best-corrected visual acuity was 20/30 or better in 96.3% of the eyes, and more than 92% of the eyes had a refraction score of ±1 D from the target refraction. The mean corneal ECD of patients before surgery was 2,803±339 cells/mm(2), which changed to 2,744±369 cells/mm(2) six months after surgery (p=0.142). CV in the sizes of endothelial cells before the surgery was 25.7%±7.1% and six months after surgery it was 25.9%±5.4% (p=0.857). CONCLUSION: Artiflex iris-fixated lens implantation is a suitable and predictable method for correction of moderate to high myopia. There was no statistically significant change in ECD and polymegathism (CV in the sizes of endothelial cells) after 6 months of follow-up.